“DEBAT RUKUN ISLAM” WAYANG GOLEK BOBODORAN PERFORMENCE - Ardiansyah Ardiansyah; Irma Savitri Sadikin; Siska Rizkiani (IKIP Siliwangi, 2019)
Wayang golek is one of world’s cultural heritage since 2003 that approved by UNESCO and counted as a puppet show. It is performed by Dalang. Dalang on the stage utters the conversation of the wayang and acts as several wayang characters at the same time. In delivering utterance dalang uses different types of tone and also some intonation. Not only to have meaning, but dalang also do it in purpose to deliver the context of the utterance. This research aims to investigate what types of tone that are used and to find out which type is mostly used. This research utilized a video of sundanese wayang golek as the source of data. It used descriptive qualitative design and discourse analysis approach. It was found that there are five types of tone, such as : rise, fall, fall-rise, rise-fall and level. Those types of tone have their own meaning depending on utterance delivery and discourse context